Manajemen Pendidikan Islam dan Atmosfer Akademik: Sebuah Tinjauan Epistemologis - Nurani, Nurani; Diana, Merita; Junaina, Junaina; Agustina, Safitri; Pahrudin, Agus; Rahman, Bujang (STKIP PGRI Bandar Lampung, 2025)
The stagnation of the academic atmosphere in Islamic educational institutions is often caused by management practices that are trapped in administrative formalities and a scientific dichotomy that separates religious knowledge from science. This study aims to deconstruct Islamic education management practices and offer a new model based on an Islamic epistemological review. This research is a qualitative library research utilizing a philosophical-pedagogical approach. Data were sourced from authoritative literature on Islamic educational philosophy and modern management, analyzed using content analysis and hermeneutics methods. The findings reveal that ideal Islamic education management must be built upon the integration of three epistemological reasonings: Bayani (textual), Burhani (rational-empirical), and Irfani (intuitive-spiritual). Bayani reasoning serves as a guardian of religious identity and ethics, Burhani reasoning encourages a culture of research and scientific innovation, while Irfani reasoning strengthens the dimensions of character and spirituality. This study recommends an